2018
DOI: 10.1111/his.13453
|View full text |Cite
|
Sign up to set email alerts
|

Histological assessment of the liver explant in transplanted hepatitis C virus patients achieving sustained virological response with direct‐acting antiviral agents

Abstract: Our study is the first to report persistent inflammation in HCV patients who received DAAs prior to LT. This supports the notion that inflammation is immunologically driven and that inflammation persists despite the absence of virus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
17
0
4

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 18 publications
1
17
0
4
Order By: Relevance
“…Until now, there have been limited published data on histologic changes in post-DAA-SVR livers. 4 In our large cohort of consecutive liver specimens from patients with chronic HCV, we show a significant decrease in inflammatory grade in post-DAA-SVR livers. However, 29% of DAA-SVR cases showed high grades (2 or 3þ) of inflammation, and 38% of DAA-SVR cases with cirrhosis continued to show a predominantly progressive pattern of fibrosis, which by definition requires septal inflammation to be present.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Until now, there have been limited published data on histologic changes in post-DAA-SVR livers. 4 In our large cohort of consecutive liver specimens from patients with chronic HCV, we show a significant decrease in inflammatory grade in post-DAA-SVR livers. However, 29% of DAA-SVR cases showed high grades (2 or 3þ) of inflammation, and 38% of DAA-SVR cases with cirrhosis continued to show a predominantly progressive pattern of fibrosis, which by definition requires septal inflammation to be present.…”
Section: Discussionmentioning
confidence: 62%
“…[1][2][3] Scant data exist on histologic changes seen after DAA therapy; studies have reported persistent inflammation and fibrosis in some patients, despite cure. 4 In addition, the impact of eliminating the virus on tumorigenesis remains controversial: achieving SVR may not necessarily correlate with a reduction in the risk of development or recurrence of hepatocellular carcinoma (HCC), especially in patients with cirrhosis. [5][6][7] During and after treatment, therapeutic response is determined by measuring serum HCV RNA levels using various nucleic acid amplification tests.…”
mentioning
confidence: 99%
“…All the patients showed decreased MHAI scores and similar or slightly decreased fibrosis stages post‐DAA treatment, and histopathologic features of AIH were not seen (Tables and ). Several of these patients had persistence of mild portal lymphocytic inflammation after DAA treatment, which has been reported …”
Section: Resultsmentioning
confidence: 59%
“…It is more difficult to assess post-SVR histopathological changes as we are no longer required to perform pre-treatment biopsies as we were in the IFN-era. However, when assessing histopathology within 2 years of treatment, though there is suggestion of fibrosis regression, persistent inflammatory activity has been observed despite the absence of the virus [20] .…”
Section: Hcv Treatment Regimensmentioning
confidence: 99%